Activity in the Fronto-Parietal and Visual Cortex Is Modulated by Feature-Based Attentional Weighting - Lanssens, Armien; Mantini, Dante; de Beeck, Hans Op; Gillebert, Celine R. (Frontiers in Neuroscience, 2022)
In day-to-day dynamic activities where sensory input is abundant, stimulus representations in the visual cortex are modulated based on their attentional priority. Several studies have established the top-down role of a fronto-parietal dorsal attention network in selective attention. In the current study, we aimed to investigate whether activity of subregions of this network and the visual cortex is modulated by feature-based attentional weighting, and if so, whether their timecourses of activity are correlated. To this end, we analyzed fMRI data of 28 healthy subjects, who performed a feature-based go/no-go task. Participants had to attend to one or two colored streams of sinusoidal gratings and respond to each grating in the task-relevant stream(s) except to a single non-target grating. Univariate and multivariate fMRI results indicated that activity in bilateral fronto-parietal (frontal eye fields, intraparietal sulcus and superior parietal lobe) and visual (V1–V4, lateral occipital cortex and fusiform gyrus) regions was modulated by selecting one instead of attending to two gratings. Functional connectivity was not significantly different between fronto-parietal and visual regions when attending to one as opposed to two gratings. Our study demonstrates that activity in subregions of both the fronto-parietal and visual cortex is modified by feature-based attentional weighting.